Migration discourses in Italy - Elena Benelli (Conserveries Mémorielles, 2013)
In the last thirty years, Italy has undergone an anthropological revolution: from a country of emigration that exported millions of emigrants around the world, it has reversed its vocation and has become a country of immigration. The presence of the newcomers on the Italian territory has not always been welcomed and integration has been problematical on diverse levels. In this article I explore how the rhetoric of the State, its laws and the media have portrayed the newcomers under the negative label of a “biblical exodus” or as a “mass invasion” (Portelli, Dal Lago) and have ineffectively managed the process of integration (Dal Lago, Parati). In order to counterbalance this inhospitable rhetoric of the State, I examine the construction of migrant’s narrative identity through the writings of some Italophone authors (Methnani, Ebri and Scego) who started to discuss issues of representation in their works and to reflect on the rapidly changing Italian society. In their works these authors “talk back” (Parati) to the host society entering a dialogic process (Bakhtin) whose mandate is to subvert prejudices and problematize the very notion of Italian national identity.